Beware of white matter hyperintensities causing systematic errors in FreeSurfer gray matter segmentations!. Issue 9 (30th March 2021) - Dadar, Mahsa; Potvin, Olivier; Camicioli, Richard; Duchesne, Simon; ,
Abstract: Volumetric estimates of subcortical and cortical structures, extracted from T1‐weighted MRIs, are widely used in many clinical and research applications. Here, we investigate the impact of the presence of white matter hyperintensities (WMHs) on FreeSurfer gray matter (GM) structure volumes and its possible bias on functional relationships. T1‐weighted images from 1, 077 participants (4, 321 timepoints) from the Alzheimer's Disease Neuroimaging Initiative were processed with FreeSurfer version 6.0.0. WMHs were segmented using a previously validated algorithm on either T2‐weighted or Fluid‐attenuated inversion recovery images. Mixed‐effects models were used to assess the relationships between overlapping WMHs and GM structure volumes and overall WMH burden, as well as to investigate whether such overlaps impact associations with age, diagnosis, and cognitive performance. Participants with higher WMH volumes had higher overlaps with GM volumes of bilateral caudate, cerebral cortex, putamen, thalamus, pallidum, and accumbens areas ( p  < .0001). When not corrected for WMHs, caudate volumes increased with age ( p  < .0001) and were not different between cognitively healthy individuals and age‐matched probable Alzheimer's disease patients. After correcting for WMHs, caudate volumes decreased with age ( p  < .0001), and Alzheimer's disease patients had lower caudate volumes than cognitively healthy individuals ( p  < .01). Uncorrected caudate volume was not associated with ADAS13 scores, whereas corrected lower caudate volumes were significantly associated with poorer cognitive performance ( p  < .0001). Presence of WMHs leads to systematic inaccuracies in GM segmentations, particularly for the caudate, which can also change clinical associations. While specifically measured for the Freesurfer toolkit, this problem likely affects other algorithms. Abstract : Presence of WMHs leads to systematic inaccuracies in GM segmentations, which can also change clinical associations. While specifically measured for the Freesurfer toolkit, this problem likely affects other algorithms.